RESEARCH ON THE FEASIBILITY OF UTILIZING SOLAR PHOTOVOLTAIC STATIONS IN PUMPING STATIONS - Nosirov Fakhriddin Jaylovovich (Western European Studies, 2024)
The possibility of using solar photovoltaic stations in pumping stations was investigated in the article. Scientific principles of designing a photovoltaic station, which can satisfy the energy demand of the consumer based on the example of a pumping station consuming 50 kW of energy per day, were presented. A consumer using 50 kW of energy per day consumes an average of 18,396,000 W of electrical energy per year. The presented photovoltaic station produces an average of 18,679,000 W of electrical energy per year. 283 kW of unused energy is supplied to the grid. Meeting the energy demand has a positive impact on the Republic's energy system. The demand for non-renewable energy resources decreases. Environmental damage is mitigated.
Keywords: demand; renewable; resources; Environmental